2016
DOI: 10.35196/rfm.2016.2.159-173
|View full text |Cite
|
Sign up to set email alerts
|

VOLATILE COMPOUNDS IN GOLDEN DELICIOUS APPLE FRUIT (Malus domestica) DURING COLD STORAGE

Abstract: Biosynthesis of volatile compounds (VC), as well as activity of related enzymes (lipoxygenase LOX, alcohol acyltransferase AAT, and alcohol dehydrogenase ADH), and fatty acids (palmitic, stearic, oleic, linoleic and linolenic acids) were assessed in Golden Delicious fruit apples (Malus domestica Borkh.) during 1 ºC storage at different atmosphere conditions. Three atmosphere conditions were used: 21 % O2 and > 1 % CO2 (Regular Atmosphere, RA), 3 % CO2 and 2 % O2 (Controlled Atmosphere, CA), and CA, with 7 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…The reason for these findings could be a lack of activity of ADH enzyme, necessary for the production of hexanol from hexanal. According to Salas and others (), the activity of ADH decreases considerably after ‘Golden Delicious’ apple has been stored for 5 mo under conventional refrigeration (the time period apples were stored before being used in this study). On the other hand, it has been suggested that the low production of volatile aroma compounds of apples stored for long periods might be due to that ADH prefers fermentative processes rather than volatile production processes (Lara and others ).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The reason for these findings could be a lack of activity of ADH enzyme, necessary for the production of hexanol from hexanal. According to Salas and others (), the activity of ADH decreases considerably after ‘Golden Delicious’ apple has been stored for 5 mo under conventional refrigeration (the time period apples were stored before being used in this study). On the other hand, it has been suggested that the low production of volatile aroma compounds of apples stored for long periods might be due to that ADH prefers fermentative processes rather than volatile production processes (Lara and others ).…”
Section: Resultsmentioning
confidence: 96%
“…This could be due to low activity of AAT enzyme. According to Salas and others (), AAT activity decreases about 50% after ‘Golden Delicious’ apples are stored under conventional refrigeration. Lara and others () also reported that storage for 6 mo induced a sharply reduction of AAT activity in ‘Mondial Gala’ apples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main precursors of VOCs in apple fruits are fatty acids that are catabolized through β-oxidation and the lipoxygenase (LOX) pathway, which produce aldehydes, alcohols, and esters. Among these, aldehydes are predominant in immature apples, whereas alcohols and esters prevail in ripe/over-ripe fruits [ 22 ]. Regarding the different investigated variables (such as apple variety, ripening stage, and yeast strain), apple variety proved to be the primary attribute influencing the quality and aroma properties of apple ciders [ 23 ].…”
Section: Discussionmentioning
confidence: 99%